Stability analysis for slope rehabilitation works at km424.80 South bound, North South expressway - Harun, Mazlan (2019)
Slope failures are major natural hazards that constantly occurred along the North South Expressway. Every year, hundreds of slope failed especially during raining seasons and causing major disruption to the network. One of them is located at slope KM424.80 South Bound. This paper is mainly to study the relationship between rainfall and slope failure at KM424.80 South Bound and the effect of rainfall toward the stability of the slope, at initial and after rehabilitation works. Site investigation works and software application developed by Geostudio, SEEP/W and SLOPE/W is used to carry out the research. The analysis method used is based on Bishop and Morgenstern-Price theory of equilibrium and entry and exit as point mode of failure. There are four types of simulations being experimented ie, FOS without any rainfall, rainfall intensity of 119mm/hour, rainfall of various intensity and FOS of using transient technique. Based on the results of the simulation, it is concluded that rain can contribute to slope failure events. However, it is not the intensity of rain that plays a role but a period of rain that contributes to slope instability. The longer the slope is exposed to the rain, the higher the risk of the slope to fail.